Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/agronomy10060917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Harvest Time on the Yield and Quality of Winter Wheat Hay Produced in Northern Italy

Abstract: The aim of this work was to study the yield and nutritional characteristics of winter wheat hay. A selection of cultivars recommended for three main purposes: grain, whole plant (biomass) and dual purpose (grain and biomass) production were cultivated and harvested from heading to grain dough stages. Yield dry weight (YDW), dry matter (DM) and undigested neutral detergent fiber (uNDF) increased with advancing maturity, ranging from 9 t ha−1, 20 and 11% of DM to 16 t ha−1, 43 and 17% of DM, respectively; while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 57 publications
(62 reference statements)
1
13
0
1
Order By: Relevance
“…The higher DML in the late milk and dough stages might be due to the altered lignin composition of whole wheat hay, which was associated with the harvest stage maturity time. In support of our results, it has been concluded that the ideal time to harvest wheat is during the late milk stage, in term of the nutritive value of wheat hay [ 34 ]. As the wheat plant matures, ADL can integrate into other nutrients, resulting in decreased nutrient digestibility.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The higher DML in the late milk and dough stages might be due to the altered lignin composition of whole wheat hay, which was associated with the harvest stage maturity time. In support of our results, it has been concluded that the ideal time to harvest wheat is during the late milk stage, in term of the nutritive value of wheat hay [ 34 ]. As the wheat plant matures, ADL can integrate into other nutrients, resulting in decreased nutrient digestibility.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, both NDF and ADF content decreased when the maturity stage increased, which corresponded with the findings of Wrobel et al [ 31 ], who reported that NDF content was lower for WCWH harvested during the dough stage compared to those during the pre-flowering stage. Further, they determined that as plants matured, grains filled with starch, which held a dilution effect on NDF content in the plant [ 34 ]. Thus, the decreased NDF and ADF content were explainable.…”
Section: Discussionmentioning
confidence: 99%
“…So, increasing fibers leads to reduce forage consumption by livestock (Ahmadi et al, 2016). In fact, highly fibered forage crops remain in the rumen for more time due to their slower rate of digestion and decreasing dry matter intake (Ronga et al, 2020). In the current study, dry matter intake in cowpea was more than in Tepary bean, which is because of the negative correlation of DMI with NDF.…”
Section: Discussionmentioning
confidence: 48%
“…=FWPP= Peso fresco de la planta -1 DWPP= Peso seco de la planta -1 , GFY= Rendimiento de forraje verde, DMY= Rendimiento de materia seca more forage yield than oats and wheat during and across the season. Crude protein is the most essential component for estimating the quality of silage especially in WFCs (Ronga et al 2020). During both the years at different locations all the WFCs at various NLs proved differences among each other for crude protein contents.…”
Section: Jamil Et Almentioning
confidence: 99%
“…The individual relationship showed strongly positive while cumulative relationship with nitrogen doses showed moderate association among variables. values of our correlation componente más esencial para estimar la calidad del ensilado, especialmente en los WFC (Ronga et al 2020). Durante los dos años y en las diferentes localizaciones, todos los WFC en varios NL demostraron diferencias entre sí en cuanto al contenido de proteína cruda.…”
Section: Jamil Et Alunclassified